Heavy metals in water and sediments of the upper course of the river Crn Drim - Hristovski, Slavčo; Jordanova, Maja; Musai, Musa; Boškovska, Violeta; Rebok, Katerina; Dinevska-Ќovkarovska Suzana; Melovski, Ljupčo (Macedonian Journal of Ecology and Environment, 2019)
Crn Drim river is the single major outflow of the outstanding Ohrid lake. Surprisingly, data on the presence of heavy metals in waters and sediments for the whole Ohrid watershed are very scarce. This study presents the data on the concentration of heavy metals Fe, Mn, Zn, Cu, Cd and Pb in both waters and sediments collected along the river Crn Drim (including Globochica reservoir), from seven sampling sites in the Republic of North Macedonia. The concentrations of analyzed heavy metals show good water quality. As far as sediments are concerned the concentrations of heavy metals are low, with the exception of sampling points at the inflows of rivers Labunishka and Vevchanska. Seasonal dynamics of heavy metals’ concentration in waters was also analyzed. Most of the heavy metals showed the lowest concentration in the spring period due to the high water levels. The annual dynamics of Fe and Mn was an exception from this pattern which might be a result of mining activities in the Ohrid Lake watershed.